PENGUATAN DUKUNGAN KELUARGA LANSIA UNTUK MENURUNKAN DERAJAT HIPERTENSI DI DUSUN MELASE - Heri Bahtiar; Maelina Ariyanti; Agus Supinganto (Stikes Yarsi Mataram, 2022)
Hypertension is a big and serious problem worldwide. The incidence ofhypertension is more and is often experienced by elderly, one factors that causehypertension, including poor diet, such as consuming foods high in sodium andfat. So that elderly who have health problems really need family support. Data onhypertension sufferers in elderly in Melase village are 30 people with an averageblood pressure of around 140/90 mmHg to 190/110 mmHg which shows that thedegree of hypertension is very high. The purpose of this service is to strengthensupport of elderly family so that it can reduce the degree of hypertension The target of this service is families who have Hypertension Elderly in Melasevillage with activities to provide education to families about the importance offamily support for elderly as well as about hypertension and prevention ofrecurrence of hypertension so that the blood pressure of th elderly is alwayscontrolled within normal limits. The activity has been carried out well according toplan, the family understands by controlling eating and psychological patterns ofelderly and gives more attention and expects similar activities to be carried outregularly in other hamlets in the same village.